EFEKTIVITAS PEMANFAATAN DANA APP DI PAROKI SANTO YOHANES RASUL WONOGIRI TAHUN 2010-2011 - Kristianto, Fajar (Jurnal Orientasi Baru, 2016)
Fast becomes one of the expressions of penance from the Christians during the Lent. Fast is an effort of mortification. Aksi Puasa Pembangunan (APP) is an act of fast in the form of alms. Through the APP, the penance is directed to build His Kingdom (compared to LG art 1). In this case, the Kingdom of God is not created by human, but it is by God. Human only participates in the process, and prepare His coming until He comes and give the fulfilment. Vision of â€œconstructingâ€ in APP is based on the self-renewal which give birth the social renewal in the society. In the period of construction, fast is directed to the actions which can lead human to his entity. APP movement enable the development of Christians to be more responsible for his own life and the society.